Gender and usage of instagram / Nurul Atiqah Mohd Azlan, Zaridah Abdullah and Jalilah Jaafar Sidek. - Mohd Azlan, Nurul Atiqah; Abdullah, Zaridah; Jaafar Sidek, Jalilah (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2017)
Social media plays such an important role in modern society that it has become an important aspect in one’s lifestyle, as well as changed the manner in which people interact and do things on a daily basis. Given rapid advancement in social media and communication technology, it is no surprise that social networking has become a key method of communication in contemporary society. A key mobile application to note is Instagram, which is widely used for personal and business purposes. In this study, quantitative method was adopted by means of a survey to elicit gender differences in the usage of Instagram for 150 Malaysian teenagers. It serves to identify gender preferences, as well as gratifications sought when using Instagram. Results indicate that the most gratification sought after by the respondents were affective needs, followed by personal and cognitive needs. There are no significant differences when it comes to personal gratifications for using Instagram between males and females in order to fulfil all of their needs. In a conclusion, although uses and gratifications theory is and old theory, it is still relevant to explain the reason people use or choose any type of media they believe are able to satisfy their needs especially with the existence of the social media.